Subscription Page (The Review of Asset Pricing Studies, 2017)
Journal Article Subscription Page Get access The Review of Asset Pricing Studies, Volume 7, Issue 2, December 2017, Page i3, https://doi.org/10.1093/rapstu/rax007 Published: 13 November 2017